An Analysis of the Death Penalty in Indonesia Criminal Law - Eddy Rifai (Faculty of Law, Sriwijaya University, Indonesia, 2017)
This research uses normative juridical approach to study on the analysis of the death penalty executions and the legal policy of death executions in Indonesia. There are delays on death executions for the convicted person since they entitled to using rights namely filing a judicial review (PK/Peninjauan Kembali). Furthermore, the legal loophole in the execution of the death penalty by the publication of the Constitutional Court Number 107 / PUU-XIII / 2015 which assert that the Attorney as the executor can ask the convicted person or his family whether to use their rights or not if the convict clearly does not want to use his rights, the executions will be carried out. Legal policy on threats and the implementation of the death penalty in the draft of criminal code was agreed by draftsman of the bill with the solutions. The draftsman of the bill agrees that the death penalty will be an alternative punishment sentenced as a last resort to protect the society. The bill also regulates that the execution among others include that the execution can be delayed by ten years probations. If the public reaction on the convict is not too large or convict has regret and could fix it or the role in the crime is not very important and there is a reason to reduce punishment, the death penalty may be changed. For pregnant women and the mentally ill convicts the execution can only be carried after the birth and the person has recovered from mental illness. The existence of this solutions is still kept putting the death penalty in criminal law, whereas the effectiveness of the death penalty is scientifically still in doubt to solve crimes and to prevent crimes by the death penalty punishment.